Strategi Pembelajaran Yang Mendukung Kemampuan Komunikasi Matematik - Siregar, Rahma Hayati (IAIN PADANGSIDIMPUAN, 2019)
Mathematical communication is the ability of a person in terms of explaining an algorithm and unique ways to solve problems, the ability of students to construct, and explain the presentation of real word phenomena in graphs, word/sentence, equation, tables or the ability of students to give assumstions about geometry image. Learning strategies that support mathematical communication skills is: Small-Group-Work Strategy, Group, Cooverative Learning, Think-Pair-Share Strategy, and Think-Talk-Write Strategy.